Understanding the new business paradigm in Eastern Europe - Kozielski, Robert (Emerald Publishing Limited, 2017)
It is beyond a doubt that the business landscape is constantly changing with every small business looking for the next competitive advantage. In Understanding the New Business Paradigm in Eastern Europe, Kozielski presents a universal model for building a successful business in these hectic times. His four-tiered model is based on lessons learned from both developed and emerging markets across Eastern Europe, and is neither limited to one type of organization or a market, nor has any geographical borders. Called the "four-leaf clover," Kozielski's model features the experiences of such companies as mBank (part of Commerzbank), Aflofarm, Atlas, Redan, Sphinx and more. This work will be of interest to academics and professional who are looking for a holistic and systematic approach to successful small business management.- Resumé vydavatel
Keywords: malé a střední podnikání -- Evropa východní; management; small and medium-sized business -- Europe, Eastern; monografie; elektronické knihy; monographs; electronic books